Karakalpaks of the Fergana Valley: Matters of Movement, Resettlement and Ethnocultural Relations - Sotvoldiyevich, Atakxanov Rafikjon (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the migration processes of karakalpaks to the Fergana valley and the involvement of Karakalpak ethnic groups in the ethnocultural processes of ethnic Uzbeks. In this article, the author describes the history of karakalpaks’ migration to the Ferghana valley, but also illustrates their location, lifestyle, traditional economic activities, and a number of ethnic characteristics in their culture. He also tried to analyze the changes in economic and cultural life of karakalpaks in the Uzbek ethnic environment and the processes of Uzbek- Karakalpak ethnointegration. The article has scientific and practical implications for a deep and in-depth study of traditional and modern interethnic processes in the Ferghana valley.